Utilization of Graded Levels of “Gayamba” Millet Pennisetum species Variety by Broiler Chickens - Tok, C. C; Dafur, B.S.; Anwo, O.J.; Datit, J.S. (Nigerian Journal of Animal Science, 2023)
An experiment was conducted to evaluate the performance, carcass characteristics and economics of broiler chickens fed diets containing graded levels of “Gayamba” millet. Five diets were formulated for both starter and finisher phases in which “Gayamba” millet replaced yellow maize at 0, 25, 50, 75 and 100% levels and the diets were designated as treatments T1, T2, T3, T4, and T5 respectively. Two hundred and twenty (220) Marshall Breed broiler chicks were randomly allotted to five dietary treatments replicated four times with eleven birds per replicate in completely randomized design. At the starter phase, which lasted for four weeks, daily feed intake (59. 09 - 59.89g) was not significantly affected by the dietary treatments. Birds on T1 had a significantly (P<0.05) lower daily weight (20.97g) than birds on T5 (23.85g). Daily weight gain was also significantly (P<0.05) influenced with birds on T5 having a value of 23.80g while T1 had a value of 20.97g. At the finisher phase, there was no significant difference across the dietary treatments. Most of the carcass parameters were not affected by dietary treatments. However, a significant (P<0.05) difference was recorded on kidney and heart for the dietary treatments. Feed cost in N/kg gain was lower (N209.33) in T5 but higher (N 237.88) in T4. It was therefore, concluded that “Gayamba” millet variety could be used as an alternative to maize in broiler diets without detrimental effect on the performance and carcass yield of broiler chickens.